Het Boschstraatkwartier-Oost 1829-1904 anders gepresenteerd - van Vugt, Thijs (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
The Boschstraat Quarter East 1829-1904: a different presentation In 2015 I defended my doctoral thesis A working class neighbourhood under the smoke of ‘De Sphinx’. A socio-spatial history of the Boschstraat Quarter East in Maastricht, 1829-1904. Originally this study was worked out in conventional historical methods, although the data were digitalized (on the basis of Excel). In this article I explore the adaptation of these data in a geographical information system: what are the possibilities and the constraints of (in my case) ArcGIS? Certainly this software offers positive effects, which above all can be seen in the visualization by the maps: better than the Excel-schedules they show the heterogeneity and variaties in the neighbourhood. Sometimes these maps guide to new questions and a different analysis. On the other hand it shows that ArcGIS also has certain limitations, as a result of which the conventional historical methods should be maintained.